1998
DOI: 10.1177/021849239800600106
|View full text |Cite
|
Sign up to set email alerts
|

Spirometric Changes following Open-Heart Surgery on Rheumatic Mitral Valves

Abstract: Evaluation of pulmonary function by spirometry in adult patients undergoing cardiacsurgery is a simple test to assess pulmonary reserve that has important implications in the operative morbidity. Pulmonary function was studied preoperatively, before discharge, and at the 3-month follow-up in 22 randomly selected patients who underwent open-heart surgery for rheumatic mitral valve disease (2 reconstructions, 20 replacements). The mean preoperative cardiothoracic ratio was 0.58. Lung function was found to be imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Different studies have correlated pulmonary functions with the functional class. 8,14 However, we in our study found that many patients (52%) were still in class II 6 months post-surgery, which did not correlate well with the improvements in PFTs at the same time. However, the PEFR did not improve at the same pace, which probably was an indication that the small airways involved in the disease process may take more time to improve.…”
Section: (►Table 5)contrasting
confidence: 67%
See 1 more Smart Citation
“…Different studies have correlated pulmonary functions with the functional class. 8,14 However, we in our study found that many patients (52%) were still in class II 6 months post-surgery, which did not correlate well with the improvements in PFTs at the same time. However, the PEFR did not improve at the same pace, which probably was an indication that the small airways involved in the disease process may take more time to improve.…”
Section: (►Table 5)contrasting
confidence: 67%
“…Chandra et al found that although there was an overall improvement in the spirometric parameters at 3 months after mitral valve replacement, the values remained lower than predicted. 14 This study results showed that by 6 months postoperative period the lung functions improved significantly, but again they also remained below the predicted values.…”
Section: (►Table 5)mentioning
confidence: 56%
“…[ 16 ] Chandra and co-workers found that there was an overall improvement in spirometric parameters at 3 months of follow-up after valve replacement, although the values remained lower than the predicted. [ 14 ] Ghosh et al have reported a significant decrease in FVC, FEV1, flow rates at 25–75% of expired vital capacity (FEF 25–75%) and maximum voluntary ventilation (MVV) in all patients at discharge. [ 15 ] In our experience, after 3 months all these parameters improved in all above the preoperative level but remained below the predicted values.…”
Section: Discussionmentioning
confidence: 99%
“…Content validity for the early developed instrument is determined through the use of panel of experts (who have more than 5 years of experience at their jobs field). A preliminary copy of the questionnaire was designed and presented to (6) experts. The data were interred into Spss (version 22) in order to describe the statistical results as follow (Frequency distribution, Bar chart, and independent t-test).…”
Section: Methodsmentioning
confidence: 99%
“…A deflated balloon attached to a catheter (a balloon catheter) is passed over a guide-wire into the narrowed vessel and then inflated to a fixed size. The balloon forces expansion of the blood vessel and the surrounding muscular wall, allowing an improved blood flow 6 . A stent may be inserted at the time of ballooning to ensure the vessel remains open, and the balloon is then deflated and withdrawn.…”
Section: Introductionmentioning
confidence: 99%